Identification of Resistance to Aflatoxin Accumulation and Yield Potential in Maize Hybrids in the Southeast Regional Aflatoxin Trials (SERAT). Issue 1 (2nd December 2016) - Wahl, Nancy; Murray, Seth C.; Isakeit, Thomas; Krakowsky, Matthew; Windham, Gary L.; Williams, W. Paul; Guo, Baozhu; Ni, Xinzhi; Knoll, Joseph; Xu, Wenwei; Scully, Brian; Mayfield, Kerry; et al.
Abstract : Aflatoxins pose a serious health hazard to humans and livestock, requiring significant economic cost in identifying and disposing of contaminated grain. Since 2003, a multi‐environmental trial of public breeding maize ( Zea mays L.) hybrids across multiple programs in the southeastern United States has evaluated accumulation of aflatoxin following inoculation with the fungus Aspergillus flavus Link. The Southeast Regional Aflatoxin Trial (SERAT) was formed to identify public germplasm with the most consistent resistance to aflatoxin accumulation and to evaluate their essential agronomic traits in different environments. Yield and related agronomic traits were evaluated in 13 locations; aflatoxin levels were evaluated in four. From 2006 to 2015, the 295 experimental hybrids, composed of varying percentages of tropical and subtropical germplasm, exhibited lower levels of aflatoxin on average at 323 versus 370 ng g −1 for the commercial checks, while the check average of 10.1 Mg ha −1 exceeded the research program average yield by 20%. Repeatability for log‐transformed aflatoxin levels exceeded 0.50 in most years, while yield was mostly above 0.75. Testing for Type II stability indicated a positive response of high‐yielding lines to better environments. The SERAT program enabled the identification of 13 top‐performing experimental hybrids that have yielded on par with or exceeded check averages and had aflatoxin levels significantly lower than check averages.